Phenotypic and Functional Analysis of Human NK Cell Subpopulations According to the Expression of FcεRIγ and NKG2C - Kim, Kyung Hwan (Front Immunol, 2019)
Human memory-like NK cells are commonly defined by either a lack of FcεRIγ or gain of NKG2C expression. Here, we investigated the heterogeneity of human CD56(dim) NK cell subpopulations according to the expression of FcεRIγ and NKG2C in a large cohort (n = 127). Although the frequency of FcεRIγ(−) and NKG2C(+) NK cells positively correlated, the FcεRIγ(−) and NKG2C(+) NK cell populations did not exactly overlap. The FcεRIγ(+)NKG2C(+), FcεRIγ(−)NKG2C(+), and FcεRIγ(−)NKG2C(−) NK cell populations were only evident after HCMV infection, but each had distinct characteristics. Among the subpopulations, FcεRIγ(−)NKG2C(+) NK cells exhibited the most restricted killer immunoglobulin-like receptor repertoire, suggesting clonal expansion. Moreover, FcεRIγ(−)NKG2C(+) NK cells exhibited the lowest Ki-67 and highest Bcl-2 expression, indicating the long-lived quiescent memory-like property. Functionally, FcεRIγ(−)NKG2C(+) NK cells had weak natural effector function against K562 but strong effector functions by CD16 engagement, whereas FcεRIγ(+)NKG2C(+) NK cells had strong effector functions in both settings. Anatomically, the FcεRIγ(+)NKG2C(+), FcεRIγ(−)NKG2C(+), and FcεRIγ(−)NKG2C(−) NK cell populations were present in multiple human peripheral organs. In conclusion, we demonstrate the heterogeneity of memory-like NK cells stratified by FcεRIγ and NKG2C and suggest both markers be utilized to better define these cells.